PostWRF: Interactive tools for the visualization of the WRF and ERA5 model outputs. (February 2023) - Nikfal, Amirhossein
Abstract: PostWRF is an open-source software toolkit to facilitate the main visualization tasks and data handling for the WRF model outputs. The toolkit is mostly written in NCL and Shell, with a namelist that resembles the WRF or WPS namelists. Besides the visualizations, PostWRF provides WRF-NetCDF to GeoTIFF conversion for GIS applications, ERA5-NetCDF reanalysis data plotting and extraction, and preparation and plotting of the RTTOV model inputs (from WRF) and outputs. The primary purpose of PostWRF is to benefit the environmental researchers (both experienced and inexperienced) to make use of the WRF model simulations, in a straightforward and efficient way, without dealing with coding and syntax errors. Since the WRF model simulates most aspects of a full atmospheric model in the regional scale, the toolkit can also be used as an educational aid in meteorological and environmental science. PostWRF is freely available on GitHub (https://github.com/anikfal/PostWRF ), provided with HTML documentations (https://postwrf.readthedocs.io/en/master ) and guided examples. Graphical abstract: Highlights: Simple and efficient tools for the WRF and ERA5 data postprocessing. RTTOV model input/output from WRF. Built mainly on NCL and Bash. Open source.